PERAN PEMERINTAH DAERAH DALAM PENGENTASAN KEMISKINAN UNTUK KESEJAHTERAAN MASYARAKAT DI DESA LAKATONG KECAMATAN MANGARABOMBANG KABUPATEN TAKALAR (Jurnal Washiyah: Jurnal Kajian Dakwah dah Komunikasi, 2025)
This study formulates two research questions: (1) the factors contributing to poverty in Lakotong Village, Manggarabombang District, Takalar Regency; and (2) the role of the local government in poverty alleviation to improve community welfare in Lakotong Village, Manggarabombang District, Takalar Regency. This research employs a qualitative approach with a descriptive method based on a social welfare perspective. The data sources consist of primary data obtained from interviews with several informants and secondary data derived from books and academic journals. Data were collected through observation, interviews, and documentation studies. The research instrument was the researcher themself. Data analysis was conducted through data reduction, data presentation, and conclusion drawing. The findings indicate that poverty in Lakotong Village is multidimensional, influenced by individual factors and cultural factors. The role of the local government in poverty alleviation in Lakotong Village can be identified through three main functions: (1) regulator, (2) dynamizer, and (3) facilitator. The implications of this study are as follows: (1) this research contributes to the development of social welfare studies, particularly in the analysis of poverty and the role of local government; and (2) this study provides guidance for social workers in designing empowerment-based interventions, strengthening community participation, and fostering synergy with local government policies to achieve sustainable welfare.